Intervention and the 'Justice Cascade': lessons from the Special Court for Sierra Leone on prosecution and civil war - Rodman, Kenneth Aaron (Human rights review, 2015)
In the ‘Justice Cascade’, Kathryn Sikkink argues that “foreign prosecutions and international tribunals can be cost-effective alternatives to military intervention.” Yet, the successes of the Special Court for Sierra Leone - in prosecuting former Liberian President Charles Taylor and in imposing accountability on the leaders of all armed groups regardless of political alignment - were dependent on a commitment by Western powers and international and regional organizations to a military victory against the rebels in Sierra Leone and coercive regime change in Liberia. The lesson that should be drawn from this case - which parallels that of other international tribunals set up during ongoing violence - is that the prospects for international criminal justice during civil wars are dependent on the political strategies adopted by outsiders to address the conflict and that taking criminal accountability seriously requires an interventionist rather than a consent-based approach to conflict resolution.